2019
DOI: 10.1002/biot.201900118
|View full text |Cite
|
Sign up to set email alerts
|

Culture on Tissue‐Specific Coatings Derived from α‐Amylase‐Digested Decellularized Adipose Tissue Enhances the Proliferation and Adipogenic Differentiation of Human Adipose‐Derived Stromal Cells

Abstract: While extracellular matrix (ECM)‐derived coatings have the potential to direct the response of cell populations in culture, there is a need to investigate the effects of ECM sourcing and processing on substrate bioactivity. To develop improved cell culture models for studying adipogenesis, the current study examines the proliferation and adipogenic differentiation of human adipose‐derived stem/stromal cells (ASCs) on a range of ECM‐derived coatings. Human decellularized adipose tissue (DAT) and commercially av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 58 publications
0
18
1
Order By: Relevance
“…There was no significant difference in the particle size distributions between the groups based on a Kolmogorov–Smirnov nonparametric test ( p < 0.05) ( Figure 3B ). To generate the coatings, applying methods previously developed by our group ( Shridhar et al, 2020 ), the particles were subsequently digested with α-amylase and homogenized in acetic acid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no significant difference in the particle size distributions between the groups based on a Kolmogorov–Smirnov nonparametric test ( p < 0.05) ( Figure 3B ). To generate the coatings, applying methods previously developed by our group ( Shridhar et al, 2020 ), the particles were subsequently digested with α-amylase and homogenized in acetic acid.…”
Section: Resultsmentioning
confidence: 99%
“…SEM analysis was used to visualize the ultrastructure of the sieved and lyophilized DNP and COL particles, as well as the DNP and COL coatings, using established protocols ( Shridhar et al, 2020 ). To visualize their interior structure, the DNP and COL coatings were scratched using a scalpel blade and then lyophilized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…New strategies that can promote the regeneration of healthy host-derived adipose tissue and enable stable and predictable volume augmentation would be of great value for a broad range of applications in plastic and reconstructive surgery. With the long-term goal of advancing towards clinical translation, our lab has been developing a broad range of off-the-shelf bioscaffolds derived from the ECM of human adipose tissue 7,8,[35][36][37] . Our previous in vivo study exploring DAT scaffolds in a subcutaneous implant model in immunocompetent rats indicated that seeding the DAT with allogeneic rat ASCs significantly enhanced blood vessel formation and remodeling of the DAT into host-derived adipose tissue 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular matrix plays an important role in modulating various cell behaviors including adhesion, proliferation and differentiation 10 . Decellularized adipose tissues have been used extensively as a promising scaffold material which provide a 3D complex ECM architecture for adipogenesis 11‐14 . Multiple strategies involving both synthetic and natural materials have been developed for soft tissue reconstruction 15,16 .…”
Section: Introductionmentioning
confidence: 99%